Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1108/et-01-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education and job creation for tourism graduates in Ghana

Abstract: Purpose -The purpose of this paper is to present a report on a tracer study conducted to find out the extent to which entrepreneurship education received by tertiary tourism graduates had been beneficial to them. Design/methodology/approach -Application of mixed methods research to collect data from 205 tertiary education graduates by the use of snowball sampling techniques and two entrepreneurship teachers selected purposively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…There are also studies available from Australia by Mitra [58], and from Africa, including Jesselyn and Mitchell in South Africa [59], Owusu-Mintah in Ghana [60], and Olokundun et al [61]. In the case of the Americas, studies were reported from Canada by Chrisman, Hynes, and Fraser [62], the United States by Dill [63], Chile by Bernasconi [64] and Argentina by Postigo, and Tamborini [65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also studies available from Australia by Mitra [58], and from Africa, including Jesselyn and Mitchell in South Africa [59], Owusu-Mintah in Ghana [60], and Olokundun et al [61]. In the case of the Americas, studies were reported from Canada by Chrisman, Hynes, and Fraser [62], the United States by Dill [63], Chile by Bernasconi [64] and Argentina by Postigo, and Tamborini [65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a number of cases (e.g. Owusu-Mintah, 2014; Packham et al , 2010; Solesvik et al , 2013), the entrepreneurship education being reviewed appears essentially to be the narrower and more traditional “enterprise for new venture creation” variety – but others recognise that there are broader possibilities. Hartshorn and Hannon (2005), for instance, note that there are “fundamental and diverse beliefs about the meaning of enterprise and entrepreneurship” (p. 616) and these include “learning for enterprise (which) aims to prepare students for survival and success in their own economic futures, “to help develop enterprising people [with] an attitude of self-reliance” […].…”
Section: The Meanings Of Entrepreneurship In Educationmentioning
confidence: 99%
“…This is probably because of the importance of investigating the development of entrepreneurship (and thus entrepreneurship education) to their respective regions, given its significance to job creation and graduate employment. Solomon (2007) indicated that the development of the education of entrepreneurship emanated from USA, and that it has since spread to the other parts of the world, including Europe (Volkmann and Audretsch, 2017), China (Li and Liu, 2011), Philippines (Velasco, 2013), Ghana (Matlay and Owusu-Mintah, 2014) and Malaysia (Ahmad and Buchanan, 2015). Entrepreneurship education contributes to the well-being of society and provides greater benefits for students who study entrepreneurship compared to those who do not attend entrepreneurship courses.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive body of research was conducted in entrepreneurship education: entrepreneurship education research (Yatu et al, 2018); entrepreneurship's influence on other disciplines (Canziani and Welsh, 2019); students' entrepreneurship-education mind-set (Cui et al, 2019); entrepreneurship education and student intention (K€ uttim et al, 2014); entrepreneurship education and job creation (Matlay and Owusu-Mintah, 2014); status of entrepreneurship education (Alakaleek, 2019).…”
Section: Introductionmentioning
confidence: 99%